2019
DOI: 10.21315/aamj2019.24.s1.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Private Saving Within Malay Community

Abstract: Few reports have indicated that majority of Malaysians do not save enough for retirement and Malays are less likely to save money as compared to other races in Malaysia. A lot of attention has been given to the link between financial literacy and saving thus neglecting other factors that are closely related to individuals. According to Bandura's (1977) theory, financial behaviour is closely related to personal factors such as individual characteristic, cognitive ability, self-efficacy, and religious faith. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…The results designate an insignificant negative direct relationship between self-efficacy and savings intention. Likewise, these findings are compatible with past research, such as Goi et al (2019), where the study examined all the factors predicting private savings and discovered that self-efficacy did not have a significant predictive impact on private savings behaviour. Therefore, this relationship is confirmed, and Hypothesis 4 is rejected.…”
Section: Perceived Behavioural (Self-efficacy)supporting
confidence: 90%
See 2 more Smart Citations
“…The results designate an insignificant negative direct relationship between self-efficacy and savings intention. Likewise, these findings are compatible with past research, such as Goi et al (2019), where the study examined all the factors predicting private savings and discovered that self-efficacy did not have a significant predictive impact on private savings behaviour. Therefore, this relationship is confirmed, and Hypothesis 4 is rejected.…”
Section: Perceived Behavioural (Self-efficacy)supporting
confidence: 90%
“…Various studies have demonstrated that peer influence has a noteworthy and positive correlation with savings behaviour such as Dangol and Maharjan (2018), Jamal et al (2015), Asmawi (2015), Kamarudin and Hashim (2018), Goi et al (2019), Alwi, Amir Hashim andAli (2015), and Syahrom et al (2017). For example, Goi et al (2019) studied the predictions of private savings within the Malay community. The objective of this study is to analyze all the factors that predict private savings.…”
Section: Subjective Norm (Peer Influence)mentioning
confidence: 99%
See 1 more Smart Citation
“…Religiosity is also found as a negative influencer of private saving (Goi et al, 2019) and an individual's preferences for risk (Eck & Nizovtsev, 2011). In many Muslim countries, people with strong Islamic religious beliefs or religiosity are less likely to purchase conventional life insurance (i.e., non-Islamic life insurance) (Chui & Kwok, 2008;Souiden & Jabeur, 2015;Zelizer, 1979), holding a belief that purchasing life insurance is disapproving of God's will (Beck & Webb, 2003).…”
Section: Religiosity (Rlg)mentioning
confidence: 99%